(untitled) (INTERNATIONAL CONFERENCE OF NATURAL AND SOCIAL-HUMANITARIAN SCIENCES, 2025)
Motivation plays a crucial role in learning a foreign language, especially in developing speaking skills. This article explores the importance of motivation in enhancing speaking abilities, different types of motivation, and effective strategies for teachers to encourage learners to speak confidently.